REVIEW OF THE MODERN NAVIGATION SYSTEMS AND FUTURE TRENDS OF THEIR DEVELOPMENT - Sushchenko, Olga A.; Yermakova, Elisabeth O.; Osipenko, Irina V. (Proceedings of National Aviation University, 2008)
Review of the modern navigation systems and their sensors is carried out. The future trends of the modern navigation systems development are considered.